Public and Private Universities in Iraq - ALFahad, Asmaa Hashem Salem; Zaidan, Nahidh Fadhil (Al-Adab Journal, 2021)
The term of mind image is one of the common terms today that its use by the success on the universities, individuals and other increases in many fields such as policy , media , social , economic , cultural institutions levels that contribute in forming the relations among the people .The relations becomes comprehensive between the image and the university learning .The study of mind image is considered a mirror that reflects the social situations .University consideration is one of the most important in the society development and an important reason in raise the society level in all culture, thinking, social, economic and aspects .The university learning is considered one of the methods of development , skills , building and preparing the material and human abilities which all sectors need to cope with society and technology development .The main objective of the university learning is to graduate the students with great abilities to serve the society and in the work market as the information are acquired by the student from the teacher and introduces it to the society in which he works in .The most important problems that confront the developed and developing countries is the problem of learning for various studying levels for the learning outputs as they are considered of the basic and educational problems in the learning system .It is one of the phenomena that threat the societies entity specially when the problem is on the level of university learning and in achieve the targeted objectives of the universities and the society in general . The university learning element are the teacher, methods of teaching, student, curriculum and study courses. The researcher used the survey method and description study that is considered one of the most suitable courses for the study scale represented in a sample of internal population such as the employees, professors and students. This study aims to learn the image of public and private universities